Beta-glucan and Grain protein studies of oats (Avena sativa L.) under temperate conditions. - Mushtaq Ahmad, Gul Zaffar, Asifa Bukhari, S.D. Mir, S.H.Dar (Electronic Journal of Plant Breeding, 2015)
The experimental material comprised of ten oats (Avena sativa L.) genotypes and their 45 F1 crosses evaluated for grain protein content, beta glucan % and grain yield (kg ha-1) . The highest grain protein content (10.75%) and beta glucan (8.56 %) were recorded for SKO-208, followed by SKO-209 and SKO-207. The highest grain yield (394 kg/ha) was recorded in SKO-208 followed by SKO-207 and SKO-209. The cross combination SKO-208 x SKO-213 recorded for the highest grain protein content (11.89 %). The cross combination SKO-208 x SKO-209 recorded the highest beta glucan (10.23 %) content while highest grain yield (43.22 kg ha-1) was observed in cross combination SKO-208 x SKO-209. The cross combinations SKO-204 x SKO-208, SKO-205 x SKO-209, SABZAAR x SKO-209, SKO-207 x SKO-208 and SKO-208 x SKO-213were observed desirable with respect to all parameters studied. Beta-glucan content was observed to have significant and positive genotypic correlation with grain protein and grain yield.